Acoustic of lightweight timber buildings: A review. (December 2017) - Caniato, Marco; Bettarello, Federica; Ferluga, Alessio; Marsich, Lucia; Schmid, Chiara; Fausti, Patrizio
Abstract: This paper presents a literature overview of the acoustic studies dedicated to lightweight wooden constructions. The reviewed articles contain prediction models, laboratory and field measurements, finite element or computational investigations as well as subjective survey describing the vibro-acoustic behaviour of a large range of wooden structures. The review analyses different type of timber constructions and investigates the acoustic research methodologies highlighting the following aspects: airborne sound insulation, impact noise reduction, flanking transmissions, human perceptions and pros and cons of the presented methods. Furthermore, an in-depth analysis of impact noise of bare floors focuses on how impact sound reduction could not be as efficient as in heavyweight constructions; the comparison between the different approaches on prediction of airborne sound insulation of multilayer timber partitions compared to traditional heavy building materials is shown. Finally a subjective method survey is provided, underlining the weakest point of timber buildings: low frequency sound insulation.